Evaluation of urban encroachment on farmland: a threat to urban agriculture in Peshawar City District, Pakistan - Samiullah, o.A.; Aslam Khan, Mohammad; Rahman, Atta-Ur; Mahmood, Shakeel (ERDKUNDE, 2019)
Peshawar is the capital city of Khyber Pakhtunkhwa (Pakistan) and the largest urban center in the province. The city is experiencing rapid urban growth which is not without its impact on urban agriculture. This paper traces the developments in the conditions of farmland in the district during the last two decades. With increasing population and economic activities, land demand for housing and other nonfarm uses like industries, commercial and transport is rising. The built-up area is expanding in all directions around the city, which is the best agricultural land except along its western side that is barren land. Therefore, any expansion in built environment has resulted and is resulting in diminishing farmland. This paper analyses how farmland has been engulfed by nonfarm uses in the process of urban expansion. An interesting fact in the case of Peshawar is that while agricultural land is being lost, some new agricultural land is also being gained. In 1991 agricultural land constituted 41 percent of the total land area of the city, which increased to about 58 percent in 1997. Nevertheless, an analysis of the land capability classes indicates that most of the gain in farmland has been in inferior class IV category, which is low in productivity while encroachment of built up area has been over the most fertile and highly productive class I category. The paper while analyzing the encroachment process also explores the policy options that are available to preserve the remaining farmland by making urban agriculture more profitable and incorporating the activity in the city plans for implementation.